Unlocking the Dynamics of Initial Public Offerings Drivers in India: The Role of Institutions, Innovation, Energy, and Resources Using ARDL and NARDL Models - Rizvi, Ifham; Nandan, Tanuj (International Journal of Economics and Financial Issues, 2025)
This study explores the dynamic link between IPO activity, country-level institutional quality and a set of dynamic macroeconomic indicators within the context of India’s emerging market from 1997 to 2022. Employing time series data, the analysis leverages both ARDL and Non-linear ARDL (NARDL) models to capture the nuances of linear and asymmetric relationships across short-run dynamics and long-run equilibrium. Results from bounds testing confirm the existence of long-run co-integration between the predictor variables and IPO activity in India. The findings reveal that institutional quality, technological innovation, and renewable energy adoption are significant positive drivers of IPO activity, signaling favorable economic conditions for firms to IPO. A marginal improvement in these factors reduces ex-ante uncertainty, increases market efficiency, and promotes better valuation incentivizing firms to pursue public listings. However, natural resource rent emerges as a negatively significant determinant, suggesting a resource curse effect in the context of IPO market performance. The study also examines the asymmetric impacts of country-level institutional quality, technological innovation, renewable energy adoption, and natural resource rent in the short- and long-term periods. Overall, the findings suggest that investor uncertainty surrounding IPO demand varies over time and across firms. This study underscores the critical role of institutional strength and dynamic macroeconomic factors in signaling-conducive environments for IPO initiation. Thus, IPO activity is expected to increase with improvements in institutional governance, support for innovation, advancement in the integration of clean energy technologies, and efficient resource management.